Fresh fruit consumption and all-cause and cause-specific mortality: findings from the China Kadoorie Biobank. (24th April 2017) - Du, Huaidong; Li, Liming; Bennett, Derrick; Yang, Ling; Guo, Yu; Key, Timothy J; Bian, Zheng; Chen, Yiping; Walters, Robin G; Millwood, Iona Y; Chen, Junshi; Wang, Junzheng; et al.
Abstract: Background: Higher fruit consumption is associated with lower risk of cardiovascular disease (CVD). Substantial uncertainties remain, however, about the associations of fruit consumption with all-cause mortality and mortality from subtypes of CVD and major non-vascular diseases, especially in China. Methods: In 2004–08, the nationwide China Kadoorie Biobank Study recruited > 0.5 million adults aged 30–79 years from 10 diverse localities in China. Fresh fruit consumption was estimated using an interviewer-administered electronic questionnaire, and mortality data were collected from death registries. Among the 462 342 participants who were free of major chronic diseases at baseline, 17 894 deaths were recorded during ∼ 7 years of follow-up. Cox regression yielded adjusted rate ratios (RRs) for all-cause and cause-specific mortality associated with fruit consumption. Results: At baseline, 28% of participants reported consuming fruit ≥ 4 days/week (regular consumers) and 6% reported never/rarely consuming fruit (non-consumers). Compared with non-consumers, regular consumers had 27% [RR = 0.73, 95% confidence interval (CI) 0.70–0.76] lower all-cause mortality, 34% lower CVD mortality ( n = 6166; RR = 0.66, 0.61–0.71), 17% lower cancer mortality ( n = 6796; RR = 0.83, 0.78–0.89) and 42% lower mortality from chronic obstructive pulmonary disease (COPD) ( n = 1119; RR = 0.58, 0.47–0.71). For each of the above, there was an approximately log-linear dose-response relationship with amount consumed. For mortality from site-specific cancers, fruit consumption was inversely associated with digestive tract cancer ( n = 2265; RR = 0.72, 0.64–0.81), particularly oesophageal cancer ( n = 801; RR = 0.65, 0.50–0.83), but not with cancer of lung or liver. Conclusions: Among Chinese adults, higher fresh fruit consumption was associated with significantly lower mortality from several major vascular and non-vascular diseases. Given the current low population level of fruit consumption, substantial health benefits could be gained from increased fruit consumption in China.